Pedagogical framing of OER—The case of language teaching - Linda Bradley; Sylvi Vigmo (Open Praxis, 2016)
This study investigates what characterises teachers’ pedagogical design of OER, and potential affordances and constraints in pedagogical design in an open education practice, when contributing to a Swedish repository Lektion.se. The teachers’ framing of the OER shared on the repository included the analyses of a delimited number of OER for learning Swedish. The analytical work with analysing what characterised the OER, was followed up with teacher interviews to explore teachers’ incentives for sharing. The OER selected for analysis were investigated linked to the features given in the repository, to identify what distinguished different categories of OER when framed by the teachers. The OER displayed a continuum of ways of framing an activity, though the majority was represented by low levels of description, which afforded less guidance. The teachers expressed a positive attitude towards sharing. The findings suggest that OER need to be defined and supported by web features to enable going beyond reuse.